Sharia Insurance Disputes Through Sharia Arbitration: A Legal Discourse - Sawitri Yuli Hartati; Sodikin (PT. Gudang Pustaka Cendekia, 2026)
Sharia insurance in Indonesia is growing, because along with the increasingly complex disputes between parties, which cannot be avoided between Islamic insurance companies and policyholders, this is even though both of them help and protect each other. The problem is regarding the legal basis for sharia insurance dispute resolution which is still scattered in several laws and regulations. This has become a discourse and issue of legal norms for sharia arbitration as an option for sharia insurance dispute resolution, and so far the resolution of sharia insurance disputes through sharia arbitration is regulated by Supreme Court Regulation Number 14 of 2016. The research method used is descriptive normative. The research method used is descriptive normative by analyzing regulations laws governing sharia dispute resolution. The results of this study explain that state policy in managing sharia insurance disputes is still a discourse, so that constitutional authority still uses Article 58 of Law no. 48 of 2009 concerning Judicial Power. Therefore, it is necessary to amend Law No. 30 of 1999, specifically regarding the article regarding the District Court, which must be supplemented by the Religious Courts and procedures for resolving disputes through sharia arbitration.